2019
DOI: 10.1016/j.nicl.2019.101900
|View full text |Cite
|
Sign up to set email alerts
|

Specific patterns of brain alterations underlie distinct clinical profiles in Huntington's disease

Abstract: Huntington's disease (HD) is a genetic neurodegenerative disease which involves a triad of motor, cognitive and psychiatric disturbances. However, there is great variability in the prominence of each type of symptom across individuals. The neurobiological basis of such variability remains poorly understood but would be crucial for better tailored treatments. Multivariate multimodal neuroimaging approaches have been successful in disentangling these profiles in other disorders. Thus we applied for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…Regarding the impact of cortical changes over functional capacity, the most significant associations were found between TFC and the motor cortex, the superior parietal, and the cuneus( Rosas et al, 2008 ). Similarly, other studies highlighted the involvement of multiple areas related to executive functions and sensorimotor and visuospatial processing in cognitive performance in HD( Garcia-Gorro et al, 2019 ). Interestingly, more recent data also point to hippocampal-dependent memory deficits in HD that cannot be solely explained as a function of degeneration in the basal ganglia( Carmichael et al, 2019 , Harris et al, 2019 ).…”
Section: Discussionmentioning
confidence: 73%
“…Regarding the impact of cortical changes over functional capacity, the most significant associations were found between TFC and the motor cortex, the superior parietal, and the cuneus( Rosas et al, 2008 ). Similarly, other studies highlighted the involvement of multiple areas related to executive functions and sensorimotor and visuospatial processing in cognitive performance in HD( Garcia-Gorro et al, 2019 ). Interestingly, more recent data also point to hippocampal-dependent memory deficits in HD that cannot be solely explained as a function of degeneration in the basal ganglia( Carmichael et al, 2019 , Harris et al, 2019 ).…”
Section: Discussionmentioning
confidence: 73%
“…Microstructural changes, as evidenced by DTI metrics FA and MD, often occur before brain atrophy and are sensitive to alterations at the cellular and molecular levels indicating brain connectivity changes that occur as fibers reorganize and/or degenerate [17,18]. DTI studies of pre-symptomatic HDGCs and/or symptomatic HD patients demonstrated increased MD compared with healthy controls in multiple brain regions, including caudate, putamen, thalamus, hippocampus, and corpus callosum [17,18,53,[103][104][105]. In this study, each of these brain areas also showed elevated MD values in late-symptomatic R6/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…LM11A-31 reduced MD to WT magnitude in the globus pallidus, the primary target of medial spiny neurons [ 106 ], and corpus callosum indicating it may prevent loss of neuronal integrity and/or axonal degeneration in these regions as it has been shown to prevent dendritic/axonal injury and p75 NTR can positively regulate myelination [ 8 , 11 , 107 – 109 ]. Concerning FA, diffusivity is reliably increased in the striatum and globus pallidum and reduced in the corpus callosum of premanifest HDGCs and manifest HD patients [ 17 , 18 , 53 , 55 , 103 , 104 , 110 , 111 ]. In this study, R6/2 mice showed FA changes in the same directions as in HD patients in the striatum, hippocampus, and corpus callosum; LM11A-31 normalized these values in the former two areas, with the greatest effect size in the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity is one of the hallmarks of HD, both in its clinical manifestations and rates of progression. Specific phenotypes are linked to patterns of brain alterations, 82,83 gender, 84 and genetic factors 85‐87 . Variability, which results in the need to recruit large numbers of patients and for prolonged periods of follow‐up, is at the forefront of obstacles to be lifted for future trials 8,88 .…”
Section: Future Challengesmentioning
confidence: 99%